2020
DOI: 10.1083/jcb.201909166
|View full text |Cite
|
Sign up to set email alerts
|

Novel phospho-switch function of delta-catenin in dendrite development

Abstract: In neurons, dendrites form the major sites of information receipt and integration. It is thus vital that, during development, the dendritic arbor is adequately formed to enable proper neural circuit formation and function. While several known processes shape the arbor, little is known of those that govern dendrite branching versus extension. Here, we report a new mechanism instructing dendrites to branch versus extend. In it, glutamate signaling activates mGluR5 receptors to promote Ckd5-mediated phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(85 citation statements)
references
References 92 publications
16
69
0
Order By: Relevance
“…Ultimately, nascent branches are either stabilized or retracted and eliminated. Distinct molecular mechanisms underlie different aspects of dendrite growth (Vaillant et al, 2002;Baumert et al, 2020;Wilson et al, 2020). For example, glutamate-mediated signaling through mGluR5 receptors leads to Ckd5-mediated phosphorylation of delta-catenin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, nascent branches are either stabilized or retracted and eliminated. Distinct molecular mechanisms underlie different aspects of dendrite growth (Vaillant et al, 2002;Baumert et al, 2020;Wilson et al, 2020). For example, glutamate-mediated signaling through mGluR5 receptors leads to Ckd5-mediated phosphorylation of delta-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, glutamate-mediated signaling through mGluR5 receptors leads to Ckd5-mediated phosphorylation of delta-catenin. Interestingly, unphosphorylated delta-catenin promotes extension, whereas phosphorylated delta-catenin favors branching over extension (Baumert et al, 2020). As a result, altering glutamate signaling can shift growth from extension to branching.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined whether endogenous MCHR1-positive cilia shortening is associated with the Accepted Article upregulation of PDLIM5 expression in dissociated rat hippocampal neurons. PDLIM5 is localized in the dendrites of cultured hippocampal neurons (75,76). However, in our immunohistochemical method, we could not detect PDLIM5-specific signals in soma and neurite in primary cultures of 18 DIV using an anti-PDLIM5 antibody with knockout-mediated validation (Supplemental Fig.…”
Section: Accepted Articlementioning
confidence: 88%
“…The PDZ domain are crucial in the formation and stability of protein complexes, establishing as important bridge between extracellular stimuli and intracellular responses [49]. It has been shown that the PDZ domain of PDLIM5 interacts with α-actinin in cardiomyocytes [30]. PDLIM5 also acts as a direct binding partner for Anion exchanger 1 (AE1) via its PDZ domain for membrane targeting [50].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that PDLIM5-PKCε interaction in the growth cone is essential for regulation of the neuronal growth cone morphology [29]. Moreover, PDLIM5 can interact with delta-catenin to form complex, which enhances dendrite branching at the expense of elongation during neuron development [30].…”
Section: Introductionmentioning
confidence: 99%